Cyberbullying: Education Research - Diana Marín Suelves; Ana Rodríguez Guimeráns; Mª Mercedes Romero Rodrigo; Silvia López Gómez (MDPI AG, 2023)
Today's society is characterised by a high degree of digitisation and the use of electronic devices at an increasingly early age. Data from recent studies and news reports from different parts of the world have focused on the malicious use of these devices by some young people to engage in peer-to-peer bullying, now known as cyberbullying. Given the negative impact of exposure to these situations on the health and well-being of children and young people, we felt it was important to analyse the scientific evidence from a dual perspective. To this end, we carried out a bibliometric study of 131 articles selected from the Scopus database using the PRISMA method to quantify the scientific literature in terms of productivity, collaboration, impact and dissemination. In addition, we carried out a content analysis to explore this polyhedral reality further through three main categories. The results made it possible to identify the places, authors, and journals where useful information can be found. We were also able to highlight the need for training for the various educational and social actors and to identify risk factors associated with cyberbullying and the importance of primary prevention.